ANALISIS PENGEMBANGAN AGROINDUSTRI BERBASIS BERAS DI PROVINSI SULAWESI TENGGARA - Augia, Rizky; Sianturi, Thesya Adelina; Ismail, Asrea Arvan Fhatan (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2025)
This study aims to formulate a development model for the rice-based agroindustry in Southeast Sulawesi. A mixed-method approach was employed, combining literature review, observations, and Focus Group Discussions (FGDs). Various respondents were involved including provincial government agencies, academic researchers, farmer group associations, and rice agroindustry actors. The study was conducted in East Kolaka Regency and Kendari City from February to June 2024. The results indicate that the potential locations for agroindustry development are in Konawe, South Konawe, Kolaka, Kendari City, and South Buton. The provision of industrial facilities and infrastructure is crucial, including dryers, hullers, polishers, sorters, silos, warehouses, and transportation infrastructure. The result also indicates various agroindustrial subsystems that consist of: (1) raw material procurement from within and outside the region, with flexible supply patterns and storage strategies based on partnerships; (2) production processes categorized into premium, medium, and low-quality rice, along with the utilization of side products such as husks and bran; and (3) marketing channels within and outside the province through direct sales and distributors. Management and financing schemes are implemented through four main approaches: a community-based economic involving cooperatives or farmer groups funded by the member, and supported by the government. ; private investment through internal capital and loans; government-managed and government-financed schemes; and Public-Private Partnership (PPP) schemes for infrastructure financing.   Key words: agroindustry subsystem, financing, management, potential location